1998
DOI: 10.1016/s0022-2275(20)32521-9
|View full text |Cite
|
Sign up to set email alerts
|

Uneven distribution of desmosterol and docosahexaenoic acid in the heads and tails of monkey sperm

Abstract: Previously we demonstrated high concentrations of desmosterol and docosahexaenoic acid (DHA, 22:6 n-3) in monkey testes and sperm. Desmosterol, a cholesterol precursor, is not present elsewhere in the body. High concentrations of DHA are found elsewhere only in the retina and brain. To examine the distribution of these compounds in the heads and tails of sperm, we separated them and determined their sterol, fatty acid, and phospholipid molecular species composition. Desmosterol predominated in tails (134.4 vs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(19 citation statements)
references
References 52 publications
0
16
1
2
Order By: Relevance
“…Our data do not support a dietary PUFA benefit to sperm membrane fluidity and flexibility (Stanley & Kenneth, ; Connor et al, ; Juan & Bayard, ; Brankatschk et al, ) either. We predicted that an increased availability of PUFA, that makes membranes more fluid (Hazel, , Holmbeck & Rand ; Brankatschk et al, ), to PF males would make their sperm membranes more elastic.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Our data do not support a dietary PUFA benefit to sperm membrane fluidity and flexibility (Stanley & Kenneth, ; Connor et al, ; Juan & Bayard, ; Brankatschk et al, ) either. We predicted that an increased availability of PUFA, that makes membranes more fluid (Hazel, , Holmbeck & Rand ; Brankatschk et al, ), to PF males would make their sperm membranes more elastic.…”
Section: Discussioncontrasting
confidence: 81%
“…In addition to lipids representing an energy source for sperm (Aziz et al, ; Lardy & Phillips, ; Mita & Yasumasu, ; Takei, Fleming, & Yanagimachi, ), dietary fats may act on sperm function in several ways. First, dietary lipids comprise sterols, which are the main building blocks for biological membranes and lipoproteins (Liu & Huang ) and affect their fluidity (Connor et al, ; Juan & Bayard, ; Carvalho et al, ; Brankatschk et al, ). Since animals, plants and fungi have very different sterols and because different sterols affect membrane properties differently (Czub & Baginski, ; Grosjean, Mongrand, Beney, Simon‐Plas, & Gerbeau‐Pissot, ), diet generally affects membrane composition and fluidity (Brankatschk et al, ; Carvalho et al, ) but also the fatty acid (FA) profile of sperm and the reproductive tract (Safarinejad, ; Comhaire et al, ; Knittelfelder et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Desmosterol has recently been found to be increased after puberty in rhesus monkeys testis (2). The same authors reported high levels of desmosterol in monkey and human spermatozoa, where desmosterol and docosahexaenoic acid was nearly exclusively confined to the flagella of monkey sperm (3,9,29). Their investigations point to a role for desmosterol in sperm motility.…”
Section: Discussionmentioning
confidence: 94%
“…The cholesterol precursor desmosterol has been found in high amounts in monkey sperm and in reproductive tissue of other animal species (2 -8). Moreover, Connor et al (9) showed that desmosterol is nearly exclusively confined to the flagella of monkey spermatozoa, thus proposing a role for this sterol in motility of spermatozoa. Relatively high concentrations of desmosterol were also described in the developing brain (10,11).…”
mentioning
confidence: 99%
“…Elimination of the ability of mice to synthesize PUFAs by disruption of the ⌬6-desaturase gene (31,32) or by inactivation of the peroxisomal ␤-oxidation (30) caused sterility in male mice, and supplementation of 22:6 (but not of 20:4) completely restored fertility and spermatogenesis (33). Most of the testicular hPUFAs accumulate in germ cells (5,6) and particularly in the sperm tail (34), which suggest a role of hPUFAs for the membrane properties of germ cells required for sperm mobility. This is of particular interest because expression of LPAAT3 is strongly up-regulated in mouse testis during puberty when spermatogenesis first occurs and then remains at a high basal level (23), thereby supporting a potential role of LPAAT3 in male fertility.…”
Section: Discussionmentioning
confidence: 99%